Design Thinking Proyek Penulisan Akademik Kontinum (PPAK) Penopang Industri Publikasi Ilmiah - Wahyudin Darmalaksana; Putri Anditasari; Hidayatul Fikra; Susanti Vera; Fitriani Fitriani (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to offer the idea of a continuum academic writing project. This research uses a qualitative approach by applying the design thinking method. The results of the research and discussion show that the continuum academic writing project is a series of student scientific publication activities starting from writing articles continuously without being limited to semesters. This research concludes that the continuum academic writing project has the potential to be a solution to the problem of publishing student scientific articles which can support the higher education scientific publication industry in Indonesia.